Application of response surface methodology(RSM) on comparative analysis of senegalia catechu dye in different mordanting conditions on cotton fabric. Issue 15 (23rd November 2022) - Boominathan, Senthilkumar; M, Sundar; V, Karthi; Magesh, G
ABSTRACT: In this research work, cotton fabrics were dyed through Senegalia Catechu dye in two different mordants conditions such as myrobalan and pomegranate rind power. Three process parameters were taken, such as dyeing temperature, dye bath pH, and mordant concentration for optimization, and other processing conditions were kept unchanged. The Box-Behnken-L15 experimental design was followed for experimentation. Regression models were generated for two different mordanting conditions, and their statistical significance was also verified through ANOVA. A comparative analysis between two mordant conditions was done through RSM analysis and found that shade variations between the two different mordanted samples were noticeable in most cases. The FTIR and SEM analysis on the dyed fabric was carried out to understand the dyeing effectiveness and chemical modification of the structure. The optimized process parameters of myrobalan mordant condition are pH level (6–7), maximum dyeing temperature (80°C), and maximum mordant concentration (25%-30%). The optimized process parameters of pomegranate rind power are pH level (9–10), moderate dyeing temperature (70°C), and maximum mordant concentration (25%-30%). These differences were interpreted due to the chemical nature of mordants, dyeing condition, raw material specification etc.